2014
DOI: 10.1186/1556-276x-9-595
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin-targeted magnetic/fluorescence micelles as a specific bi-functional nanoprobe for imaging liver tumor

Abstract: In order to delineate the location of the tumor both before and during operation, we developed targeted bi-functional polymeric micelles for magnetic resonance (MR) and fluorescence imaging in liver tumors. Hydrophobic superparamagnetic iron oxide nanoparticles (SPIONs) were loaded into the polymeric micelles through self-assembly of an amphiphilic block copolymer poly(ethylene glycol)-poly(ϵ-caprolactone). After, transferrin (Tf) and near-infrared fluorescence molecule Cy5.5 were conjugated onto the surface o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Jin et al reported a bifunctional probe for targeting and imaging liver cancer, but this was only achieved in vitro [20]. In addition, Hui et al only achieved dual-modality imaging in heterotopic liver tumors [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Jin et al reported a bifunctional probe for targeting and imaging liver cancer, but this was only achieved in vitro [20]. In addition, Hui et al only achieved dual-modality imaging in heterotopic liver tumors [21]. …”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated that SPPTC offered outstanding targeting on the MRI and uorescence imaging. 191 Yan et al studied targeting specicity of the anti-a v b 3 antibody through molecular MRI imaging. 192 They fabricated a PEG modied Fe 3 O 4 core.…”
Section: Metal Oxide-based Cancer Diagnostics and Imaging Technologie...mentioning
confidence: 99%
“…In order to achieve liver tumor imaging with bi‐functional nanoprobes, Qi et al117 encapsulated SPIONs into PEG‐poly(ε‐caprolactone) (PEG‐ b ‐PCL) polymeric micelles, that were then decorated with Tf and the NIR fluorescent dye Cy5.5 to produce nanosized SPIO@PEG‐ b ‐PCL‐Tf/Cy5.5 (SPPTC). No expression of TfR mRNA in the HL7702 normal cell line was observed, while there was good expression in the HePG2 carcinoma cells.…”
Section: Cancer Cell Surface Marker Targetingmentioning
confidence: 99%